Tribological research of leaf‐surface wax derived from plants of Pinaceae. (1st August 2018) - Feng, Xin; Hu, Yichao; Xia, Yanqiu
Abstract: Two kinds of leaf‐surface waxes are extracted from the leaves of Picea wilsonii Mast (PM) and Pinussylvestris (PS) and used as additive in synthetic ester base oil. The tribological properties were investigated using an MFT‐R4000 tribology tester at room temperature. Gas chromatography‐mass spectrometry analysis was performed to identify the composition of the PM and PS leaf‐surface wax, and scanning electron microscopy and time of flight secondary ion mass spectrometry were used to investigate friction mechanisms. The results suggest that the leaf‐surface wax of PM and PS could successfully reduce the friction and wear of steel‐aluminium and steel‐steel sliding pairs as compared with synthetic ester containing Terpineol additives. The excellent tribological properties were attributed to the protective film generated on the worn surfaces by leaf‐surface wax during the friction process.